Creative and Learning Processes using Game-Based Activities - Inchamnan, Wilawan; Yampray, Karuna (Journal of Reviews on Global Economics, 2017)
This paper gains a better understanding of how gameplay activities facilitate the creative learning process, reviews learning objects as game elements that influence creativity and learning outcomes, and focuses on learning activity in terms of a series of actions, namely goals, action and interaction, and interpretation. The series should be an element of object learning through game elements, that are adapted from a collection of content items, practice items, and assessment within game tasks. The findings illustrate the relationship between the series of actions within classroom activities, show the significant impact of learning outcomes and the series of actions' learning, and facilitate creative learning processes. The paper proposes a method for understanding the relationships between the learning processes that players undertake during gameplay, and the components of the game that allow these processes to occur. This method was synthesized from the focus group by considering the relationships of their learning outcomes and creative processes within game activities. Previous research studied the creative potential in puzzle game play in the process. The pilot participants in the study adapted the process that was observed during the game "Online Gunz 2: The Second Duel", and were recorded their learning outcomes. The anticipated outcomes represented how video games foster learning processes and creative processes. The results illustrate a significant conceptual method as interrelationships between meaningful learning and creative potential within a game-based activities.